International Ethics and Responsibility to Protect - Kabat-Rudnicka, Danuta (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2017)
The article examines a new institution of international law that has taken shape since the beginning of the 21st century: the responsibility to protect. This responsibility is interpreted in the light of theories of international relations and international ethics. In the article, analytical and descriptive research methods have been applied. While the relatively new institution of the responsibility to protect has, due to its importance, gained fairly widespread acceptance in the international community, it has also been criticised as too difficult to implement. Nevertheless, it deserves our attention as the most radical programme legitimising actions taken under the auspices of the United Nations to protect the civilian population when it is facing threat.